Listening to the stones : essays on architecture and function in ancient Greek sanctuaries in honour of Richard Alan Tomlinson - Partida, Elena; Partida, Elena; Schmidt-Dounas, Barbara; Schmidt-Dounas, Barbara; Tomlinson, Richard Allan (Archaeopress Archaeology, 2019)
'Listening to the Stones' deals with a range of topics that relate to the broad scope of Richard Tomlinson's archaeological quests and echoes his own methodology in research. Innovative masonry modes, matters of style and orders, proportions and design principles, as well as the inter-regional connections which fostered the transmission of architectural traditions and technical know-how have been cardinal points in Tomlinson's writings and lectures, as much as the Greek foundations on foreign soil, the forethought in planning, achievements in the field of engineering and the interaction between the secular, the sepulchral and the sacred premises in an ancient city. The conservative or progressive attitudes of a society usually leave an imprint on architectural creations. So, architecture is subject to evolution along with the developing societies